Hexagonal columnar liquid crystals as a processing additive to a P3HT:PCBM photoactive layer. (27th August 2015) - T. N., Ahipa; K. M., Anoop; Krishna Pai, Ranjith
Abstract : Trihydrazone-functionalized cyanopyridine liquid crystals are introduced into the photoactive layer as processing additives to acquire an improved interpenetrating network and charge carrier mobility. Abstract : Morphology of the donor/acceptor network in the photoactive layer is critical in order to optimize the device performance. In the present study, a new trihydrazone-functionalized cyanopyridine (CPTH-D16) demonstrating an ambient temperature hexagonal columnar liquid crystalline phase is introduced into the well-known photoactive layer i.e. P3HT:PCBM as a processing additive towards the construction of an efficient solar cell. Photon absorption and emission properties of the blends in the solution/film state are systematically investigated by UV-visible and fluorescence spectroscopy. Furthermore, surface morphology, the degree of crystallinity, changes in nanostructure, and the conductivity of blend films are determined through epi-fluorescence and atomic force microscopy. It is observed that the addition of the CPTH-D16 liquid crystal drastically increases the TUNA current passing through the P3HT:PCBM film. Here, the structural anisotropic nature of CPTH-D16 material helps to obtain well-ordered morphology with nanostructured crystallite formation as well as enhanced current in the P3HT:PCBM film.